Reliability and Validity of the Velotron Racermate Cycle Ergometer to Measure Anaerobic Power - Astorino, T. A.; Cottrell, T. (International Journal of Sports Medicine, 2012)
This study assessed the reliability and validity of the Velotron Racermate™ cycle ergometer to assess anaerobic power. Men (9 cyclists and 13 recreationally-active) and women (17 recreationally-active and 1 cyclist) (age=24.7±4.2 yr) performed 2 Wingate tests on the Velotron or 3 Wingate tests (2 on the Velotron and 1 on the Monark Peak Bike) over a 7–14 day period. Peak power, mean power, minimum power, fatigue index, heart rate, and peak and minimum cadence were assessed. Results revealed significant test-retest reliability for mean power (r=0.90, p<0.01), minimum power (r=0.79, p<0.05) and peak power (r=0.70, p<0.05) with repeated bouts on the Velotron. Peak power was significantly higher (p<0.05) on the Velotron (9.95±1.39 W/kg) vs. the Monark (9.13±1.26 W/kg); however, mean power was higher (p<0.05) on the Monark (6.95±0.89 W/kg) vs. the Velotron (6.11±0.52 W/kg and 6.25±0.59 W/kg). Data reveal significant reliability for mean and peak power from the Velotron Racermate, yet multiple variables differ between the Velotron and the Monark mechanically-braked cycle ergometer.
Keywords: Wingate test; PCr; fatigue index; supramaximal exercise